Tasks Facing European Transport Policy in the 21st Century - Wolf Tietze; Marie-Luise Steinmann-Tietze (Promet - Traffic&Transportation, 1970)
The remarkable rise of Europe following the NapoleonicWars during the early JIY' centwy favouring the spread of therailway systems and- subsequent to this new mode of transport-leading to almost complete industrialisation and urbanisationin the political frame of nation states has suffered severe setbacksduring the 2rJ' century deplorably highlighted by WorldWar I and World War Jl, by various civil wars and the ColdWar, by lwge scale expellations, and substantial alternations ofpolitical borders. At the same time much has changed, toothroughout the extensive continental regions around Europe.Consequently, prospects for future development in the 21' centwydiffer widely. Extraordinary effort is demanded to satisfysocial expectations not known so far avoiding, howeve1~ bothnew warlike conflicts and additional exploitations of the naturalenvironment. To solve this task traffic plays a key role by optimalevaluation of all its modes and by applt:cation of the besttechnical achievements along with stepwise adaptation of theurban settlements which represent the most important locationsof living and working.